On Determinantal recurrence relations of banded matrices - Zhibin Du; Carlos Fonseca; António Pereira (Kuwait Journal of Science)
We provide an algorithm based on a less-known result about recurrence relations for the determinants of banded matrices. As a consequence, we prove recent conjectures on the determinants of particular classes of pentadiagonal matrices and simple alternative proofs for other results.